2005 IEEE Aerospace Conference 2005
DOI: 10.1109/aero.2005.1559302
|View full text |Cite
|
Sign up to set email alerts
|

Investigation Organizer: the development and testing of a Web-based tool to support mishap investigations

Abstract: InvestigationOrganizer (IO) is a collaborative web-based system designed to support the conduct of mishap investigations. IO provides a common repository for a wide range of mishap related information, and allows investigators to make explicit, shared, and meaningful links between evidence, causal models, findings and recommendations. It integrates the functionality of a database, a common document repository, a semantic knowledge network, a rule-based inference engine, and causal modeling and visualization. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…Moreover, calls for a "Pragmatic Web" (that explicitly enables communities to test, refine, and implement emergent, experience-based, solutions) counterbalance the purely deductive nature of much contemporary knowledge representation (such as in ontologies for the Semantic Web) [22]. Empirical studies of collaborative inquiry in investigative settings, notably [23], have indicated user desire for (a) the ability to link information artifacts to the reasoning processes in which they figure, as an aid to keeping a community informed about the state of its knowledge, (b) the ability to generate "big picture" reports, and (c) minimizing ontological complexity. Some extant tools accomplish a few of these objectives: [24] provides a utility for describing observations, beliefs, and uncertainty associated with online documents using semi-formal semantic markup; [25] enables communication of user-created and automatically generated "knowledge maps" in document analysis applications.…”
Section: Tools In Support Of Communicative Inquirymentioning
confidence: 99%
“…Moreover, calls for a "Pragmatic Web" (that explicitly enables communities to test, refine, and implement emergent, experience-based, solutions) counterbalance the purely deductive nature of much contemporary knowledge representation (such as in ontologies for the Semantic Web) [22]. Empirical studies of collaborative inquiry in investigative settings, notably [23], have indicated user desire for (a) the ability to link information artifacts to the reasoning processes in which they figure, as an aid to keeping a community informed about the state of its knowledge, (b) the ability to generate "big picture" reports, and (c) minimizing ontological complexity. Some extant tools accomplish a few of these objectives: [24] provides a utility for describing observations, beliefs, and uncertainty associated with online documents using semi-formal semantic markup; [25] enables communication of user-created and automatically generated "knowledge maps" in document analysis applications.…”
Section: Tools In Support Of Communicative Inquirymentioning
confidence: 99%
“…To illustrate the procedures of the model, we use a portion of the NASA Investigation Organizer's (IO) ontology, which is designed to rectify any mishap in the conducting of investigations [24]. IO offers a common repository for a broad assortment of mishaprelated data.…”
Section: Motivational Examplementioning
confidence: 99%
“…A subset of the described functionality has been implemented in the SISel system [5]. Another system with related functionality aimed at the spacecraft accident investigation domain was built at NASA by Carvalho et al [6,7].…”
Section: Motivating Scenariomentioning
confidence: 99%